Implementation of a Smart Classroom: An IoT-Based Projector Control System Using the Priority Logic Override Control Method - Husain T; Santi Santi (Universitas Muslim Indonesia, 2026)
The development of the Internet of Things (IoT) has driven the automation of electronic devices in educational environments, particularly classrooms and laboratories. One of the important devices in the learning process is the LCD Projector, which is often inefficient due to user negligence in turning the device on or off. Another problem is the frequent delay in the start of the learning process due to the remote not working to turn on the LCD Projector. This study aimed to implement the Priority Logic Override Control method in an IoT-based LCD Projector control system to increase the efficiency and flexibility of device control. The proposed system utilizes an ESP8266 microcontroller as a control center, a Passive Infrared (PIR) sensor as a user presence detector, and a relay module as an actuator to control the projector's power. The Blynk application was used as a smartphone-based user interface via a Wi-Fi network and a cloud server. The Priority Logic Override Control method is applied to prioritize manual user control over automatic sensor-based control. This method operates by assigning higher control priority to override other control commands automatically. The implementation results show that the system operates in real time, responsively, and reliably in managing the projector’s status according to room conditions and user commands. Additionally, the system improves energy efficiency in the use of LCD projectors and reduces the startup time of the learning process in classrooms or laboratories.